Integration of probe systems in a nanopositioning and nanomeasuring machine - Jäger, Gerd; Manske, Eberhard; Hausotte, Tino; Mastylo, Rostyslav; Büchner, Hans-Joachim; Grünwald, Rainer; Füßl, Roland (Proceedings Volume 5776, 8th International Symposium on Laser Metrology, 2005)
The paper describes the design of a high-precision three-deminsional nanopositioning and nanomeasuring machine (NPM-Machine). The NPM-Machine has been developed by the Institute of Process Measurement and Sensor Technology of the Technische Universitat Ilmenau and manufactured by the SIOS MeBtechnik GmbH Ilmenau. The machine was successfully tested and continually improved in the last few years. The NPM-Machine has a resolution of less than 0,1 nm over the entire positioning and measuring range of 25 mm x 25 mm x 5 mm. An Abbe offset-free design and the application of a new concept for compensating systematic errors resulting from mechanical bearings provide extraordinary accuracy. An important part of the NPM-Machine is constituted by a mirror corner. The integration of several probe systems and Nanotools makes the NPM-Machine suitable for various tasks, such as large-area scanning probe microscopy, mask and wafer inspection, nanostructuring, biotechnology as well as measuring mechanical precision workpieces a.s.o. Various probe systems have been integrated into the NPM-Machines. The machines are operating successfully in several German and foreign institutes including the Physikalisch-Technische Bundesanstalt (PTB). The article gives basic information on the NPM-Machine and describes the mode of operation and the measurements by means of probe systems.
Keywords: three-dimensional positioning and measuring machine; Abbe-offset; probe systems